A RANDOMIZED CLINICAL STUDY TO EVALUATE THE EFFECTS OF INTRATHECAL MAGNESIUM SULFATE VERSUS DEXMEDETOMIDINE AS AN ADJUVANT TO HYPERBARIC BUPIVACAINE HYDROCHLORIDE IN SUBARACHNOID BLOCK FOR INFRAUMBILICAL SURGERIES - ANUPAMA KUMARI; SARA MARY THOMAS; DINESH CHAUHAN (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: The objective is to compare the efficacy of intrathecal magnesium sulfate versus intrathecal dexmedetomidine as an adjuvant to 0.5% hyperbaric bupivacaine in terms of spinal anesthesia characteristics and postoperative analgesia in patients undergoing infra-umbillical surgeries. Methods: In this randomized clinical trial, hundred adult patients in the age group of 18–65 years, belonging to the American Society of Anesthesiologists grade 1 and 2, posted for infra-umbilical surgeries under subarachnoid block were included. Patients were randomly divided into two groups of 50 each after obtaining Hospital ethical committee approval and Informed consent. Group M (50 patients) was given Inj. Bupivacaine hydrochloride 0.5% (heavy) 15 mg+Inj. Magnesium Sulfate 50 mg (0.1 mL) and Group D (50 patients) were given Inj. Bupivacaine Hydrochloride 0.5% (heavy) 15 mg+Inj. Dexmedetomidine 5 μg (0.1 mL). Hemodynamic parameters, onset, and duration of sensory blockade, time taken to reach the highest dermatomal level (T1) of sensory blockade, time taken to achieve motor blockade (Modified Bromage score 3), duration of sensory analgesia (Regression to L1), time to complete motor block recovery and duration post-operative analgesia were recorded. Results: Time taken for onset of sensory block, to achieve the highest dermatomal level of sensory blockade, onset of motor block and to achieve Bromage score 3 were less in Group D as compared to that of Group M (p<0.0001). The total duration of sensory blockade and motor block was longer in Group D (p<0.0001). The Visual Analog Scale score when the patients complained of pain for the 1st time in post-operative period, was significantly lower in Group Das compared to Group M (p=0.016). There was no significant difference in the rate of complications such as nausea, vomiting, bradycardia, and hypotension in both the groups. Conclusion: Intrathecal Dexmedetomidine as an adjuvant to hyperbaric bupivacaine in subarachnoid block significantly quickens the onset of sensory and motor blockade. It also prolongs the duration of sensory block, motor block, and post-operative analgesia.